Preparation of MgB₂ and BSCCO superconducting thin films / Nur Helmi @ Nur Jannah Azman … [et al.] - Ahmad, Mardiana; Makhtar, Nurulizzati; Baha, Azlina (Research Management Institute (RMI), 2013)
The main purpose of this project is to prepare MgB2 and BSCCO superconductor bulk samples and thin films, and also to determine the highest critical temperature for MgB₂ and BSCCO superconductor. In order to prepare the MgB2 and BSCCO superconductor, the solid state method will be applied which involve the process of grinding and sintering. The produced sample will be compress into pellet form before it is being sintered. The MgB₂ bulks were prepared by a pellet-in-sealed tube at different annealing temperatures of 650°C, 700°C, 750°C and 800°C. The superconducting thin films were prepared using sputtering technique. The bulk and thin film samples were then be characterized in various methods; electrical measurement, ac magnetic susceptibility measurement, Scanning Electron Microscopy (SEM) and also phase purity and composition by X-ray diffraction (XRD). For MgB₂ superconductor bulk samples, AC susceptibility measurements showed a sharp superconducting transition in all samples. The critical current density (Jc) was measured using ac magnetic susceptibility measurement method. The highest critical density in magnetic field, JC(T,H) from the magnetization measurements was recorded for the 650°C annealed MgB₂. X-ray diffraction (XRD) analysis showed small quantities of MgO and unreacted Mg phases as impurities in the samples which act as effective pinning centres for vortices. Unreacted Mg decreased with increasing annealing temperature…